Biblical Money and the Church's Mission in the Digital Age - Guild, Stuart V. (Sekolah Tinggi Teologi Teologi Simpson Ungaran, 2025)
This article examines the relationship between biblical money principles and the mission of the church in the digital age, focusing on Bitcoin as a form of